On the strengthening of three-leaf stone masonry walls - Silva, Rui André Martins (2008)
This paper is devoted to the experimental characterization of the structural behaviour of three-leaf stone ma-sonry walls. The first part of the experimental results described here was presented during the last SAHC Conference (Oliveira et al. 2006). In total ten walls, plain and strengthened resorting to transversal tying, in-jection and both techniques applied simultaneously, were tested aiming at capturing the detailed structural be-haviour. Globally, all strengthening techniques described here showed to be effective in different ways.